ANALISIS RISIKO PADA PROYEK JALAN LINGKAR UTARA BREBES - TEGAL - Nadya Shafira Salsabilla; Kartono Wibowo; Hermin Poedjiastoeti (Politeknik Negeri Semarang, 2021)
Risk is a consequence of uncertain conditions. Risk will always exist in every construction project because basically a construction project is a unique, dynamic and risky activity. The purpose of this research is to analyze the risks in the construction project of the North Ring Road Brebes - Tegal and the purpose of this study is to identify risks, conduct risk level assessments and handle high risks that affect the project. This study uses two data, namely secondary data and primary data. Primary data, namely risk identification data, risk level data and risk response data. Secondary data, namely organizational structure data. The data that has been obtained are then analyzed using the Probability and Impact Matrix (PIM) method and followed by calculating the risk level value. Based on this value, the category and ranking of each risk is then determined. In the last stage, analysis of the handling of the highest risk is carried out. The results of the risk identification analysis of this study obtained 33 risks, then the results of the analysis using the Probability and Impact Matrix (PIM) method obtained 3 (three) high risks, namely incomplete design data, conflicts of interest with residents, inadequate project information (soil testing and reports survey). Ten risks fall into the moderate category and 20 other risks fall into the low category.